Peran Firm Size, Current Ratio, Debt To Asset Ratio, dan Return On Equity Terhadap Price To Book Value Pada Perusahaan Telekomunikasi Yang Terdaftar di Bursa Efek Indonesia Periode 2014-2020 - Fitri Melati Sukma (Improvement: Jurnal Manajemen dan Bisnis, 2021)
Technological developments have made telecommunications companies listed on the Indonesian Stock Exchange experience very rapid growth, this makes investors interested in investing in telecommunications companies. But there are problems in the variables studied because the differences between theory and facts are not in line, this is what makes researchers interested in choosing the title for research. This research analysis model used multiple linier regression analysis with data processing using EVIEWS 9. Hypothesis test using t-test and f-test with a significance level of 0,05. The results showed that Firm Size, Current Ratio, Debt to Asset Ratio and Return on Equity had effect on Price to Book Value. The result of the t test show that the variables Firm Size have no effect on Price to Book Value, variable Current Ratio, Debt to Asset Ratio, and Return on Equity have effect on Price to Book Value. Coefficient determination is 69,85%.Perkembangan teknologi menjadikan perusahaan telekomunikasi yang terdaftar di Bursa Efek Indonesia mengalami pertumbuhan yang sangat pesat, hal ini menjadikan para investor tertarik untuk berinvestasi pada perusahaan telekomunikasi. Namun terdapat masalah pada variabel yang  diteliti karena terdapat perbedaan antara teori dengan fakta tidak sejalan, hal inilah yang membuat peneliti tertarik untuk memilih judul tersebut untuk diteliti. Model analisis penelitian ini menggunakan analisis regresi linear berganda dengan pengolahan data menggunakan EVIEWS 9. Uji hipotesis menggunakan uji t dan uji f dengan tingkat signifikannya sebesar 0,05. Hasil penelitian ini menunjukkan bahwa Firm Size, Current Ratio, Debt to Asset Ratio, dan Return on Equity berpengaruh terhadap Price to Book Value. Dengan dilakukan uji t menunjukkan bahwa variabel Firm Size tidak berpengaruh terhadap Price to Book Value, variabel Current Ratio, Debt to Asset Ratio, dan Return on Equity berpengaruh terhadap Price to Book Value, koefisien determinasinya sebesar 69,85%.Keywords: Firm Size, Current Ratio, Debt to Asset Ratio, Return on Equity, Price to Book Value